Lidar characterization of the Arctic atmosphere during ASTAR 2007: four cases studies of boundary layer, mixed-phase and multi-layer clouds - Lampert, A.; Ritter, C.; Hoffmann, A.; Gayet, J.-F.; Mioche, G.; Ehrlich, A.; Dörnbrack, A.; Wendisch, M.; Shiobara, M. (Atmospheric Chemistry and Physics, 2010)
During the Arctic Study of Tropospheric Aerosol, Clouds and Radiation (ASTAR), which was conducted in Svalbard in March and April 2007, tropospheric Arctic clouds were observed with two ground-based backscatter lidar systems (micro pulse lidar and Raman lidar) and with an airborne elastic lidar. In the time period of the ASTAR 2007 campaign, an increase in low-level cloud cover (cloud tops below 2.5 km) from 51% to 65% was observed above Ny-ÃÂlesund. Four different case studies of lidar cloud observations are analyzed: With the ground-based Raman lidar, a layer of spherical particles was observed at an altitude of 2 km after the dissolution of a cloud. The layer probably consisted of small hydrated aerosol (radius of 280 nm) with a high number concentration (around 300 cmÃ¢ÂÂ3) at low temperatures (Ã¢ÂÂ30 ÃÂ°C). Observations of a boundary layer mixed-phase cloud by airborne lidar and concurrent airborne in situ and spectral solar radiation sensors revealed the localized process of total glaciation at the boundary of different air masses. In the free troposphere, a cloud composed of various ice layers with very different optical properties was detected by the Raman lidar, suggesting large differences of ice crystal size, shape and habit. Further, a mixed-phase double layer cloud was observed by airborne lidar in the free troposphere. Local orography influenced the evolution of this cloud. The four case studies revealed relations of cloud properties and specific atmospheric conditions, which we plan to use as the base for numerical simulations of these clouds.